Povezanost med slogi navezanosti in razumevanjem dvoumnih elektronskih sporočil - Cugmas, Zlatka; Šendlinger, Tjaša (Revija za elementarno izobraževanje, 2018)
The relation between attachment styles and understanding of ambiguous electronic messages. The goal of this research was to examine the relation between attachment styles and interpretation bias in response to electronic messages in a sample of 184 undergraduates. A new vignette measure of interpretation bias in the context of nine electronic messages was developed (Cugmas, unpublished work). Participants selected one of the four responses that we assumed were related to four attachment styles. We applied the Inventory of Parent and Peer Attachment (Armsden & Greenberg, 1987), the Adult Attachment Scale (Collins, 1996) and the Relationship Questionnaire (Bartholomew & Horowitz, 1991). The results partly support our hypothesis, since interpreting ambiguous electronic messages in a negative manner is associated with insecure attachment styles.DOI: 10.18690/rei.11.3.215 -232.2018COBISS-ID: 24275720
Keywords: students; attachment; ambiguous electronic messaging; attachment styles